Post-traumatic Growth and Psychological Resilience During the COVID-19 Pandemic: A Serial Mediation Model - Li, Qi; Hu, Jinsheng (Frontiers in Psychiatry, 2022)
Although the WHO has issued guidelines for managing to contain, mitigate, and limit of the COVID-19. However, it is more essential to highlight the urgency and importance of evaluating social functioning and mental health status during the pandemic. College students have experienced serious problems and have had to overcome many negative situations brought about by the pandemic. Accordingly, the present study intends to use Chinese college students as sample to observe the positive adoption and changes during the ongoing COVID-19. Guided by literatures in this filed, we explored the positive effect of post-traumatic growth on psychological resilience, and considered about mediation roles of positive coping styles and cognitive reappraisal. A total of 463 college students from universities in China effectively completed online questionnaires. The result showed that these four variables were positively correlated with each other (ps < 0.001). More importantly, our findings proved a direct and positive effect on psychological resilience. Positive coping styles and cognitive reappraisal, respectively, mediated the relationship between post-traumatic growth and psychological resilience. Also, serial mediation existed among those variables: students with high-level post-traumatic growth tended to report increased use of positive coping strategies, which further facilitated their cognitive reappraisal, and subsequently, promoted their psychological resilience. The findings obtained in this study will provide a theoretical basis and possible viable strategies for both targeted crisis intervention and psychological trauma recovery plans.